Breeding ecology, population size and nest site preferences of red-billed tropicbirds at St Helena, South Atlantic Ocean - Beard, Annalea; Madeiros Mirra, Renata; Clingham, Elizabeth; Henry, Leeann; Thomas, Robert J.; Hailer, Frank (Emu - Austral Ornithology, 2023)
We describe the population size and breeding ecology of the Red-billed Tropicbird, Phaethon aethereus, a poorly studied pantropical seabird, at St Helena, South Atlantic. The population size of 81–246 pairs and 272–564 individuals identifies the study population as the largest colony of Red-billed Tropicbirds in the South Atlantic, but also an internationally important part of the global population. We estimated the survival from laying to fledging of 158 nests between 2004 and 2017 at only 33%, among the lowest values reported globally for the species. Most nest failures occurred during incubation, with predation identified as the predominant cause of fledging failure. Intervals between breeding attempts were longer after successful nesting attempts than failed attempts. Previous breeding interval and nest cavity fidelity further influenced the interval between breeding attempts, while the presence of replacement clutches did not. Multiple nest site and cavity characteristics were important predictors of cavity use, nest site selection and productivity. Management options for reducing mammalian predators to ensure the long-term viability of this important population at St Helena are discussed.